Analisis Komprehensif Implementasi Kurikulum Merdeka di SMKN 2 Sawahlunto - Hutabarat, Rinto; Febrina, Rifka; Yani, Nurmaningsih; Rahmi, Sri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
In education, the curriculum is a key element that determines the success of the learning process. The implementation of the Merdeka Curriculum is carried out on vocational competencies which are expected to serve as insights and guidelines in improving the practical abilities of vocational students in pursuing education. Curriculum implementation is reflected in learning activities at school. As part of educational reform in Indonesia with the hope of creating graduates who are better prepared to face the challenges of the times, the curriculum currently implemented is an independent curriculum. Not only in public schools, but the independent curriculum is also applied to vocational high schools. In vocational high schools (SMK), there are characteristics of a skills-based and vocational curriculum so that the results of this study reveal how the Merdeka Curriculum is adapted in vocational education and how its application can prepare students with relevant skills in the world of work. This research was conducted using a descriptive qualitative method with the resource persons being the principal, teachers, and students. The data collection technique uses the Miles and Huberman Technique. The results showed that the implementation of Merdeka curriculum was analyzed in terms of input, process, and output. Then the positive impacts and challenges are also analyzed in this study.